Prevalence and social determinants of malnutrition in children under 5 years affiliated to the SISBEN of the urban area of the municipality of Palermo in Colombia, 2017 - Barrera-Dussán, Nathaly; Fierro-Parra, Eder Pablo; Puentes-Fierro, Leidy Yohana; Ramos-Castañeda, Jorge Andres (Universidad y Salud, 2018)
Introduction: Malnutrition includes undernourishment, overweight and obesity generated by food imbalance and the presence of social determinants of health (SDH) that mainly affects the child population. Objective: To identify the prevalence of malnutrition and its association with SDH in children under 5 years belonging to Sistema de Beneficiarios para Programas Sociales (SISBEN) program from the urban area of the municipality of Palermo. Materials and methods: A cross-sectional study with an analytical approach was conducted. The sample was 254 children under 5 belonging to the SISBEN and residents of the urban area of the municipality of Palermo. Socioeconomic information was collected by a survey and nutritional classification by anthropometric valuation. Results: 6.7% showed malnutrition by deficit and 9.8% by excess. Association between chronic malnutrition with overcrowding (P = 0.03; RP = 1.9 IC: 95% 1.138 – 3.173) and low economic income was found (p = 0.004; RP = 1.96 IC: 95% 1.22 – 3.15); as well as between acute malnutrition and inadequate disposal of waste (P = 0.03; RP = 6 IC: 95% 4.2 – 8.7);and between global malnutrition with low economic income (P = 0.02; RP = 2.2 IC: 95% 1.11 – 4.35) and inadequate housing (p = 0.03; RP = 2.08 IC: 95% 1.06 – 4.06). Conclusions: The two extremes of malnutrition coexist: by excess and by defect. The latter is related to overcrowding, low family income and inadequate disposal of rubbish.